The Role of DISKOMINFO in Accelerating Development Smart City Development in Samarinda City - Deandlles Christover; Aji Syarif Hidayatullah; Alfin Ananda; Achmad Fawwaz Albani (Manunggal Halim Jaya, 2024)
This study aims to analyze the role of the Department of Communication and Informatics (DISKOMINFO) in accelerating the development of the smart city initiative in Samarinda, and to provide recommendations for further improvement. As the capital of East Kalimantan Province and a key economic hub, Samarinda recognizes the importance of adopting technology to enhance public services and create a sustainable environment. A qualitative approach was employed to understand DISKOMINFO's role in the smart city initiatives. Primary data sources included DISKOMINFO employees, relevant stakeholders, and the community involved in the smart city projects. Informants were selected purposively. Data collection involved in-depth interviews with DISKOMINFO staff, stakeholders, and selected community members, along with the analysis of official documents and reports related to the smart city initiatives. The data was analyzed using content analysis to identify patterns, themes, and relationships between concepts. The findings indicate that DISKOMINFO plays a crucial role in coordinating, implementing, and overseeing smart city initiatives in Samarinda. The study also reveals that while significant progress has been made in certain areas, further efforts are needed to improve inter-agency collaboration, enhance technological capacity, and increase active community participation. The results of this research are expected to serve as a reference for policymakers in strengthening sustainable smart city initiatives in Samarinda. Penelitian ini bertujuan untuk menganalisis peran Diskominfo Kota Samarinda dalam akselerasi pembangunan smart city dan memberikan rekomendasi untuk perbaikan lebih lanjut. Hasil penelitian diharapkan memberikan wawasan berharga bagi pengambil kebijakan, akademisi, dan masyarakat dalam mendukung visi smart city yang berkelanjutan di Kota Samarinda. Penelitian ini menggunakan pendekatan kualitatif untuk memahami peran Dinas Komunikasi dan Informatika (Diskominfo) dalam akselerasi pembangunan smart city di Kota Samarinda. Sumber data primer mencakup seluruh pegawai Diskominfo, pemangku kepentingan terkait, dan masyarakat yang terlibat dalam inisiatif smart city. Pemilihan informan dilakukan secara purposive. Teknik pengumpulan data melibatkan wawancara mendalam dengan pegawai Diskominfo, pemangku kepentingan, dan masyarakat terpilih, serta analisis dokumen resmi dan laporan terkait smart city. Analisis data menggunakan pendekatan analisis isi untuk mengidentifikasi pola, tema, dan hubungan antar konsep. Hasilnya diharapkan memberikan pemahaman mendalam tentang peran Diskominfo dan dampaknya dalam pembangunan smart city di Kota Samarinda